Diabetes Mellitus in Outpatients in Debre Berhan Referral Hospital, Ethiopia - Tesfa Dejenie Habtewold; Wendwesen Dibekulu Tsega; Bayu Yihun Wale (Journal of Diabetes Research)
Introduction. Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Most people with diabetes live in low- and middle-income countries and these will experience the greatest increase in cases of diabetes over the next 22 years. Objective. To assess the prevalence and associated factors of diabetes mellitus among outpatients of Debre Berhan Referral Hospital. Methods and Materials. A cross-sectional study was conducted from April to June 2015 among 385 patients. Random quota sampling technique was used to get individual patients and risk factors assessment. Patients diabetes status was ascertained by World Health Organization Diabetes Mellitus Diagnostic Criteria. The collected data were entered, cleaned, and analyzed and Chi-square test was applied to test any association between dependent and independent variable. Result. Out of the total 385 study patients, 368 have participated in the study yielding a response rate of 95.3%. Concerning clinical presentation of diabetes mellitus, 13.3% of patients reported thirst, 14.4% of patients declared polyurea, and 14.9% of patients ascertained unexplained weight loss. The statistically significant associated factors of diabetes mellitus were hypertensive history, obesity, the number of parities, and smoking history. Conclusion. The prevalence of diabetes mellitus among outpatients in Debre Berhan Referral Hospital was 0.34% and several clinical and behavioral factors contribute to the occurrence of diabetes mellitus which impose initiation of preventive, promotive, and curative strategies.